Juridical Review of Termination of Employment Due to Covid-19 on Workers or Laborers in Banten Province - Suandi, Suandi; Muchtar, Andhyka (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The COVID-19 pandemic has affected many industrial companies in Banten Province, resulting in a wave of layoffs for workers/laborers in Banten Province. The company that terminates the employment relationship of the employee on the grounds of Force Majeur or coercive circumstances. The purpose of this study was to determine the legal review of Termination of Employment Due to COVID-19 for Workers in Banten Province. The method used in this study is a normative legal research method, with a statute approach and a conceptual approach. Legal material is analyzed by induction and interpretation syllogism. The results of the analysis show that: The Juridical Review of Termination of Employment Due to COVID-19 on Workers in Banten Province, is still not in accordance with existing policies, because the company terminates employment on the grounds of "force majeure" caused by the pandemic COVID-19, but the provisions in Article 164 paragraph (1) of the Manpower Act stipulate that the reason for layoffs due to "force majeure" can only be applied if the company has suffered losses for 2 (two) consecutive years, while the pandemic COVID-19 has only been around for a year